TLR3 Agonist Amplifies the Anti-Inflammatory Potency of ADSCs via IL-10-Mediated Macrophage Polarization in Acute Pancreatitis - Jianxing Liu; Wenjing Yan; Shanshan Chen; Yingjie Sun; Fangfang Zhang; Yue Yang; Liang Jin (Stem Cells International)
The immunoregulatory role of mesenchymal stem cells (MSCs) in inflammation is heterogeneous and can exhibit anti-inflammatory or proinflammatory properties depending on the microenvironment. We herein observed that the activation of Toll-like receptor 3 (TLR3) by polyinosinic : polycytidylic acid (poly(I : C)) stimulation facilitated the transformation of adipose-derived stem cells (ADSCs) into an anti-inflammatory phenotype. The enhanced anti-inflammatory properties were assessed in a taurocholate-induced pancreatitis model. The results demonstrated that poly(I : C) pretreated ADSCs exhibited enhanced anti-inflammatory properties than untreated ADSCs in taurocholate-induced pancreatitis. Mechanistically, poly(I : C)-treated ADSCs showed increased production and secretion of interleukin-10 (IL-10), which demonstrates a potent ability to alleviate inflammatory signaling cascades in acinar cells. Simultaneously, the heightened anti-inflammatory effects of poly(I : C)-treated ADSCs in pancreatitis were associated with the regulation of macrophage classical/alternative transformation, thereby mitigating inflammatory factor-mediated damage to the pancreatic acinar cell. We propose that TLR3 activation by poly(I : C) is an effective strategy to enhance the anti-inflammatory properties of MSCs, which offers a valuable consideration for improving the therapeutic efficacy of MSCs in inflammatory diseases.